A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae) - Shattuck, Steve (Zootaxa, 2009)
The Australian species belonging to the ant genus Myrmecina are revised. The genus was found to contain thirteen species, eleven of which are described here for the first time. The species include M. alpina sp. n., M. australis Wheeler and Wheeler, M. difficulta sp. n., M. eruga sp. n., M. inaequala sp. n., M. pumila sp. n., M. rugosa Forel, M. silvalaeva sp. n., M. silvampla sp. n., M. silvangula sp. n., M. silvarugosa sp. n., M. silvatransversa sp. n. and M. wesselensis sp. n. The majority of species are found in coastal Queensland with two also occurring in eastern New South Wales and one restricted to the Northern Territory. Several species are known from very limited regions and one is only known to occur above approximately 1000m, making these some of the most restricted and high-elevation specialist ants known from Australia.